Need Analysis of Arabic Language Model Design for Islamic Law - Ummu-Hani Abas; Mohammad Najib Jaffar; Azlan Shaiful Baharum; Abdul Manan Ismail; Ahmad Asyraf Mat Ali; Rasmina Hasbullah (Human Resource Management Academic Research Society, 2024)
Indexed by ERA